Evaluating the triboelectric performance of trimethylolpropane trioleate grease - Nur Aisya Affrina, Mohamed Ariffin; Lee, Chiew Tin; Haris Ahmad, Israr Ahmad; William Chong, Woei Fong (Malaysian Tribology Society., 2024)
The study compared the triboelectric performance of trimethylolpropane trioleate (TMPO) grease with perfluoropolyether (PFPE) grease, both formulated with polytetrafluoroethylene (PTFE) as a thickener. Thermogravimetric analysis (TGA) revealed that TMPO grease exhibits 8.8% better thermal stability than PFPE grease. TMPO grease shows a 22.1% improvement in friction over PFPE without electricity. Under a 2 A current flow, both greases show reduced frictional performance, though the TMPO grease maintains a 9.8% lower friction compared to PFPE. The better friction performance of TMPO is attributed to its conductivity compared to PFPE, despite both greases utilizing a non-conductive PTFE thickener.